No-Way Out: Being Entrapped in Wedlock Plays of Alan Ayckbourn: How the Other Half Loves and The Garden - Eda Bayrakçı (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Alan Ayckbourn using traditional devices of farcical comedy can be depicted as a farceur, yet via breaking the conventions, How the Other Half Loves and The Garden turn into a tragedy of the married who became victims within their dissatisfactory marriage. The characters initially drawn as stereotypes develop into characters entrapped in marriage through their monologues including emotions. Ayckbourn has a mastery in employing displacement of time and place to illustrate the desperation in middle-class marriage via modelling entrapped married couples on stage. Although marital dissatisfaction, infidelity, lack of communication between couples are serious problems in modern world, Ayckbourn’s presenting this problem humorously makes him outstanding among his contemporaries. Ayckbourn visualizes hypocritical faces of the married from different perspectives changing in accordance with the sphere. House is the sphere where prisoners of marriage bond are trapped while garden depicted as the outside of marriage both literally and metaphorically is the sphere where married imprisoners can escape from the burdens and the hardships of marriage. The purpose of this paper is to show central themes of marital dissatisfaction, infidelity and escapists manners of Ayckbourn’s characters illustrated vividly by Ayckbourn through his skillful observation and employing traditional devices to break the conventions.